Hajj Pilgrims' Abandonment: The Protection for Consumer (Case of PT Anugrah Karya Wisata Utama and PT Abu Tours & Travel) - Sekar Arum Rahmawati (Journal of Law and Legal Reform, 2021)
People are encouraged to selectively choose a trusted umroh travel agency. First Travel and Abu Travel has violated Article 65 letter a Government Regulation Number 79 Year 2012 on Implementation of Law Number 13 Year 2008 regarding Hajj Implementation. The violation is a neglect of Umrah pilgrims who failed to leave for Saudi Arabia, and resulted in material and immaterial losses experienced by Umrah congregation. The type of legal research used by the authors in this study is the type of legal case study research; This type of research is also called Library Research, is research conducted by tracing or reviewing and analyzing library materials or materials ready to use documents. Improving the supervision of umrah. The supervision is done because it can increase the travel agency of umroh and haj pilgrimage, so that with this supervision the prospective pilgrims who register will not get the act of fraud.